Analysis of entropy generation in an MHD flow over a rotating porous disk with variable physical properties. (2015) - Rashidi, Mohammad Mehdi; Mahmud, Shohel; Freidoonimehr, Navid; Rostami, Behnam
In this study, we perform the second law of thermodynamics analysis of a rotating porous disk in the presence of a magnetic field with temperature-dependent thermo-physical properties numerically using fourth-order Runge-Kutta method. Entropy generation equations are derived as a function of velocity and temperature gradients. An excellent agreement for the skin friction coefficients and the rate of heat transfer can be observed between the current data and the published results presented by other researchers in literature. The obtained results demonstrate the average entropy generation rate decreases for the decreasing trend of the magnetic interaction parameter (M), temperature difference parameter (ε), suction parameter (Ws), Brinkman number (Br) and the increasing trend of Reynolds number (Re). This simulation shows the feasibility of using magnetic rotating disk drives in novel nuclear space propulsion engines and also this model has important applications in heat transfer enhancement in renewable energy systems and industrial thermal management.